Induction and pore-formed stages in Al2Au's dealloying process in HCl solutions. (1st April 2021) - Yan, Z.C.; Guo, L.Y.; Chen, Q.; Zhang, H.; Chen, X.Y.; Kim, K.B.; Zhang, L.C.; Wang, W.M.
Graphical abstract: Highlights: Two stages can be distinguished in dealloying process of Al2 Au ribbon. Multi-resolution analysis on OCP is performed in an innovative way. The Al2 Au first undergoes local corrosion and then global corrosion. Abstract: Two stages, induction stage and pore-formed stage, were distinguished in Al2 Au's dealloying process in HCl solutions by OCP, SEM and XPS characterization. In induction stage, the Au state with binding energy 85.4 eV (labelled as Al2 Au (I)) was transformed into the state 84.7 eV (Al2 Au (II)); in pore-formed stage, nanoporous structure started to be formed, Al2 Au (II) and residual Al2 Au (I) were transformed into the state 83.7 eV (pure Au). Multi-resolution analysis on OCP noise revealed that the induction stage and pore-formed stage undergo different corrosion modes: the former is local corrosion and the latter is global corrosion.